PENGEMBANGAN SIS+ KONSULTASI SEBAGAI MONITORING PELAYANAN DOSEN DAN MAHASISWA STUDI KASUS: STMIK RAHARJA - Ary Budi Warsito; Untung Rahardja; Dwi Maya Suhainingsih (CCIT Journal, 2017)
Among some professors are always confronted with students who are not just one or two students but many students. And among students who often meet has the same name but sometimes these lecturers often forget to the name of the student. The problem is when a student with the same name that asked for the second time to the lecturer in question and certainly the lecturer will be trying to remember the last time the students and professors meet. This led to work being impeded. And when the student asking the answer to the question ever asked questions first and the Professor forgot what ever the student ask, this will backfire for the lecturer. The system developed in the form of this is online, so that professors could do consultation anytime anywhere and anytime. The method used is descriptive method with identifying problems in advance, in addition to the development model used by researchers in the form of analysis of the problems of the waterfall to the maintenance phase of the program. In this system a student do create tickets, the tickets are obtained by given to the lecturer to conduct consultation. This system is applied with students and lecturers can have a history about the guidance that has been done so that lecturers did not forget when was the last student conduct guidance. This system generates data guidance which can be printed.